Changes in North Atlantic atmospheric circulation in a warmer climate favor winter flooding and summer drought over Europe - Rousi, Eftychia; Selten, Frank M.; Rahmstorf, Stefan (Prof. Dr.); Coumou, Dim (Dr.) (Journal of Climate, 2021)
Changes in atmospheric circulation under increasing greenhouse gas concentrations are important because of their implications for weather extremes and associated societal risks. However, uncertainties in models and future projections are still large and drivers behind circulation changes are not well understood. Particularly for Europe, a potential weakening of the Atlantic meridional overturning circulation (AMOC) is considered important as it affects SST patterns and ocean-atmosphere heat fluxes and, subsequently, European climate. Here we detect and characterize changes in atmospheric circulation patterns over the North Atlantic under increasing CO2 concentrations in simulations of a very high-resolution, fully coupled climate model (CM2.6) with a realistic representation of the AMOC. We use an objective clustering technique (self-organizing maps) and validate the model's clusters against reanalysis data. We compare the frequency of those patterns in a CO2 doubling experiment, characterized by an AMOC decline, with those in a preindustrial run, and find statistically significant changes. The most robust findings are 1) a similar to 30% increase in zonal flow regimes in February, relevant for flood risk in northwestern Europe, and 2) a similar to 60% increase in anticyclonic (high pressure) circulation directly west of the United Kingdom in August, relevant for western and central European drought. A robust decrease in the frequency of Scandinavian blocking is also seen across most months and seasons. Despite the uncertainties regarding atmospheric circulation response to climate change, our findings contribute to the increasing evidence for the emergence of robust high-impact changes over Europe.